Authoritarian protectionism and the post-neoliberal transition: learning from Stuart Hall’s method of articulation - Luke Cooper (Frontiers in Political Science)
This article returns to Stuart Hall’s account of Thatcherism to consider the interaction between consent-based hegemonic devices and the structural compulsions that emanate from political-economic transitions. It argues that Hall’s method of articulation offers a middle position in analysing contemporary authoritarian trends, which recognises the role of structural constraints and logics, as well as the discursive construction of ideology in enabling (and inhibiting) hegemony seeking efforts. Building on existing work that has highlighted the distinction between classical neoliberal arguments regarding economic individualism and the trend towards ‘protectionist’ discourses today, where the state is cast as a protector of the in-group against threats, real and imagined, the article outlines how the method of articulation can aid us in making sense of the complexity and non-linearity of the post-neoliberal transition. This framework is then applied to the case study of the British Conservative Party’s trajectory after the 2016 Brexit referendum.